Fresno County Bar Association Wilkin Luncheon - Watkins, Howard::::::::: (1984)
Judge Hollis Best, Jeannie Best, Bernard Witkin, Alba Witkin, Judge James V. Paige, Robert Sears Witkin looking at Robert Sears